Assessing Mechanical Properties of Hot Mix Asphalt with Wire Wool Fibers - Ahmed N. Bdour; Yahia Khalayleh; Aslam A. Al-Omari (Advances in Civil Engineering)
This paper investigates the potential application of wire wool in the modification of hot asphalt mixes (HMA). Wire wool material is widely available at local markets as a by-product of wire wool industry and as waste products from homes. For the purpose of this study, wire wool was cut into small pieces so that it can be placed in the asphalt mixes. Different percentages of wire wool were incorporated with the hot asphalt mixes (0.0%, 0.25%, and 0.5%) of the total weight of the asphalt binder. Various experimental tests were used to evaluate the modification effectiveness of combining wire wool with hot asphalt mixes, namely, the Marshall Stability, indirect tensile strength (ITS), dynamic creep, fatigue, and rutting tests. Test results proved that the addition of wire wool increased the tensile strength of the asphalt concrete mixes. However, rutting increased due to increasing percentage of wire wool. Therefore, mixes containing wire wool can be used in areas where rutting is not the expected predominant distress type.